Hubungan Self-Efficacy dengan Tingkat Stres dalam Menyusun Tugas Akhir pada Mahasiswa Fikes Universitas Abulyatama - Gadis Zahratul Oula; Urip Pratama; Nurul Amna (Lembaga Pengembangan Kinerja Dosen, 2024)
The problems experienced by students in completing thesis turn into negative feelings and tend to cause loss of motivation, lack of self-confidence, and stress in students. This study aims to analyze the correlation of self-efficacy with stress levels in completing a thesis on students at the Faculty of Health Sciences, Universitas Abulyatama. This study used an analytical design with a cross-sectional approach. It involved 173 college students as the sample chosen using a total sampling technique. This study was carried out on May 28th - June 13th, 2024 by using a self-efficacy questionnaire with a Croncbach Alpha value of 0,864 and a DASS-21 Croncbach Alpha value of 0,75. The data analysis used a chi-square test. The results indicate that most students experienced moderate stress levels as much as 79 students (45,7%) and had moderate self-efficacy as much as 73 students (42,2%), with a ρ value of 0,000. This study shows the correlation between self-efficacy and students' stress levels at the Faculty of Health Sciences, Universitas Abulyatama. Further, the university should boost students' motivation and self-efficacy in completing a thesis to prevent stressful occurrences.